2007
DOI: 10.1128/jvi.00417-07
|View full text |Cite|
|
Sign up to set email alerts
|

A Baculovirus-Expressed Dicistrovirus That Is Infectious to Aphids

Abstract: Detailed investigation of virus replication is facilitated by the construction of a full-length infectious clone of the viral genome. To date, this has not been achieved for members of the family Dicistroviridae. Here we demonstrate the construction of a baculovirus that expresses a dicistrovirus that is infectious in its natural host. We inserted a full-length cDNA clone of the genomic RNA of the dicistrovirus Rhopalosiphum padi virus (RhPV) into a baculovirus expression vector. Virus particles containing RhP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
(53 reference statements)
0
13
0
1
Order By: Relevance
“…Positive-strand RNA viruses exhibit comparatively higher mutation rates because of the lack of proofreading machinery, template switching, and other factors which could have contributed to our difficulties. However, previous use of this method with Rhopalosiphum padi virus (RhPV) showed that non-virus nucleotide insertions at the 5' and 3' UTR termini had no effect on the ability to produce infectious virus (Pal et al 2007). Whether our deletions had an impact on translation was not determined.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Positive-strand RNA viruses exhibit comparatively higher mutation rates because of the lack of proofreading machinery, template switching, and other factors which could have contributed to our difficulties. However, previous use of this method with Rhopalosiphum padi virus (RhPV) showed that non-virus nucleotide insertions at the 5' and 3' UTR termini had no effect on the ability to produce infectious virus (Pal et al 2007). Whether our deletions had an impact on translation was not determined.…”
Section: Resultsmentioning
confidence: 89%
“…At present, there is no available means of propagating infectious SINV-3 particles in vitro, which has hampered its evaluation and development as a microbial insecticide. However, Pal et al (2007) successfully produced a similar virus, Rhopalosiphum padi virus (RhPV) (Picornavirales: Dicistroviridae), in quantity with a recombinant baculovirus system capable of expressing the entire genome of the virus in surrogate insect cells. As there is no available cell line for fire ants, and the method had been established for a similar virus, baculovirus-driven expression seemed to be a viable solution to the production of SINV-3.…”
mentioning
confidence: 99%
See 3 more Smart Citations